Pembentukan Identitas Santri dalam Politik - Abidin, Min Hajul (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2019)
The purpose of the study is to find out How identity politics conducted by santri’s. Through a qualitative approach with the subject amounted to 2 people. The results of this study prove that both subjects developed their political capacity through parliamentary struggle and amoeba political strategy by spreading to strategic posts. In addition there is a unique identity that santri have when plunging in politics, where identity as a santri is a pride because it has more value than other politicians who plunge in politics. In addition to this, politics is also regarded as a way of worship and khodamul ummah, not solely because of the position.